Quantification of the ion transport mechanism in protective polymer coatings on lithium metal anodes. Issue 20 (21st April 2021) - Zhou, Hongyao; Liu, Haodong; Xing, Xing; Wang, Zijun; Yu, Sicen; Veith, Gabriel M.; Liu, Ping
Abstract : Protective Polymer Coatings (PPCs) protect lithium metal anodes in rechargeable batteries to stabilize the Li/electrolyte interface and to extend the cycle life by reducing parasitic reactions and improving the lithium deposition morphology. Abstract : Protective Polymer Coatings (PPCs) have been proposed to protect lithium metal anodes in rechargeable batteries to stabilize the Li/electrolyte interface and to extend the cycle life by reducing parasitic reactions and improving the lithium deposition morphology. However, the ion transport mechanism in PPCs remains unclear. Specifically, the degree of polymer swelling in the electrolyte and the influence of polymer/solvent/ion interactions are never quantified. Here we use poly(acrylonitrile- co -butadiene) (PAN–PBD) with controlled cross-link densities to quantify how the swelling ratio of the PPC affects conductivity, Li + ion selectivity, activation energy, and rheological properties. The large difference in polarities between PAN (polar) and PBD (non-polar) segments allows the comparison of PPC properties when swollen in carbonate (high polarity) and ether (low polarity) electrolytes, which are the two most common classes of electrolytes. We find that a low swelling ratio of the PPC increases the transference number of Li + ions while decreasing the conductivity. The activation energy only increases when the PPC is swollen in the carbonate electrolyte because of the strong ion–dipole interaction in the PAN phase, which is absent in the non-polar PBD phase. Theoretical models using Hansen solubility parameters and a percolation model have been shown to be effective in predicting the swelling behavior of PPCs in organic solvents and to estimate the conductivity. The trade-off between conductivity and the transference number is the primary challenge for PPCs. Our study provides general guidelines for PPC design, which favors the use of non-polar polymers with low polarity organic electrolytes.